Coronavirus disease 2019 (COVID-19) excess mortality outcomes associated with pandemic effects study (COPES): A systematic review and meta-analysis - Lu, David; Dhanoa, Sumeet; Cheema, Harleen; Lewis, Kimberley; Geeraert, Patrick; Merrick, Benjamin; Vander Leek, Aaron; Sebastianski, Meghan; Kula, Brittany; Chaudhuri, Dipayan; Basmaji, John; Agrawal, Arnav; et al. (Frontiers in Medicine, 2022)
Background and Aim: With the Coronavirus Disease 2019 (COVID-19) pandemic continuing to impact healthcare systems around the world, healthcare providers are attempting to balance resources devoted to COVID-19 patients while minimizing excess mortality overall (both COVID-19 and non-COVID-19 patients). To this end, we conducted a systematic review to describe the effect of the COVID-19 pandemic on all-cause excess mortality (COVID-19 and non-COVID-19) during the pandemic timeframe compared to non-pandemic times. Methods: We searched EMBASE, Cochrane Database of Systematic Reviews, MEDLINE, Cumulative Index to Nursing and Allied Health Literature (CINAHL) and Cochrane Controlled Trials Register (CENTRAL), from inception (1948) to December 31, 2020. We used a two-stage review process to screen/extract data. We assessed risk of bias using Newcastle-Ottawa Scale (NOS). We used Critical Appraisal and Grading of Recommendations Assessment, Development and Evaluation (GRADE) methodology. Results: Of 11,581 citations, 194 studies met eligibility. Of these studies, 31 had mortality comparisons (n=433,196,345 participants). Compared to pre-pandemic times, during the COVID-19 pandemic, our meta-analysis demonstrated that COVID-19 mortality had an increased risk difference (RD) of 0.06% (95% CI: 0.06-0.06% p<0.00001). All-cause mortality also increased (relative risk [RR]: 1.53, 95% CI: 1.38-1.70, p<0.00001) alongside non-COVID-19 mortality (RR: 1.18, 1.07-1.30, p<0.00001). There was “very low” certainty of evidence through GRADE assessment for all outcomes studied, demonstrating the evidence as uncertain. Interpretation: The COVID-19 pandemic may have caused significant increases in all-cause excess mortality, greater than those accounted for by increases due to COVID-19 mortality alone, although the evidence is uncertain.